2017
DOI: 10.3390/ijms18122511
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Pro-Cognitive and Antiamnestic Properties of Berberine and Magnoflorine Isolated from Barberry Species by Centrifugal Partition Chromatography (CPC), in Relation to QSAR Modelling

Abstract: Civilization diseases associated with memory disorders are important health problems occurring due to a prolonged life span. The manuscript shows the results of an in vivo study targeting the emergence of two drug candidates with anti-amnestic properties. The preceding quantitative structure–activity relationship (QSAR) studies provided information on the ability of berberine and magnoflorine to cross the blood–brain barrier (BBB). In the light of these findings, both compounds were purified from crude plant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 35 publications
(53 reference statements)
2
39
0
Order By: Relevance
“…20 botanical families such as Papaveraceae, Berberidaceae, Annonaceae, Aristolochiaceae, Lauraceae, Monimiaceae, Menispermaceae, and others [2][3][4] (Table 1) among the representatives of ca. 20 botanical families such as Papaveraceae, Berberidaceae, Annonaceae, Aristolochiaceae, Lauraceae, Monimiaceae, Menispermaceae, and others [2][3][4] (Table 1). [35] MGN itself can be perceived as the most widely distributed aporphine compound.…”
Section: Chemistry and Pharmacokinetics Of Magnoflorinementioning
confidence: 99%
See 1 more Smart Citation
“…20 botanical families such as Papaveraceae, Berberidaceae, Annonaceae, Aristolochiaceae, Lauraceae, Monimiaceae, Menispermaceae, and others [2][3][4] (Table 1) among the representatives of ca. 20 botanical families such as Papaveraceae, Berberidaceae, Annonaceae, Aristolochiaceae, Lauraceae, Monimiaceae, Menispermaceae, and others [2][3][4] (Table 1). [35] MGN itself can be perceived as the most widely distributed aporphine compound.…”
Section: Chemistry and Pharmacokinetics Of Magnoflorinementioning
confidence: 99%
“…Certainly, it is an interesting alkaloid characterized by the presence of two hydroxyl-and two methoxyl-substituents attached to an aporphine structure that occurs naturally in various plant species with distant etymology. Structurally, it is a direct derivative of (S)-corytuberine in which the nitrogen atom has been quaternized by another methyl group, and as the result of this process, MGN occurs in the plants in the form of a quarternary ammonium ion with high polarity and good water solubility [3,4,36,37]. From the phylogenetic point of view, MGN resembles the structure of aristolochic acid derivatives [7].…”
Section: Botanical Familymentioning
confidence: 99%
“…Unfortunately, the authors of this study did not perform comparisons using a positive control. Magnoflorine (49) (20 mg/kg, administered intraperitoneally) alone enhanced cognition, and coadministration of magnoflorine with scopolamine blocked long-term, but not short-term, memory impairment (Kukula-Koch et al 2017). However, no explanation of the active principle or mechanisms of action was provided and use of a positive control was lacking.…”
Section: Other Central Effectsmentioning
confidence: 99%
“…However, although several mechanisms were envisioned to explain the role of (S)-norcoclaurine synthase, its mechanism is still matter of debate. Interestingly, (S)norcoclaurine is transformed into about 2500 identified benzoisoquinoline alkaloids, including the analgesic morphine, the antitussive noscapine, the muscle relaxant tubocurarine, the vasodilator papaverine and the antioxidant magnoflorine (Hagel and Facchini 2013), the latter being a by-product known to cross the blood-brain barrier and possess a marked central activity characterized by cognitionenhancing properties probably due to its ability of inhibiting acetylcholinesterase activity (Kukula-Koch et al 2017). Haber et al (1997) reported that, in the rat brain, ethanol induces the formation of (S)-norcoclaurine, also recognized as a potential precursor of morphine in Papaver somniferum L. (Brochmann-Hanssen 1984).…”
Section: (S)-norcoclaurinementioning
confidence: 99%